[1992] Proceedings of the 12th International Conference on Distributed Computing Systems
DOI: 10.1109/icdcs.1992.235009
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end scheduling to meet deadlines in distributed systems

Abstract: In a distributed system or communication network tasks may need to be executed on more than one processor. For time-critical tasks, the timing constraints are typically given as end-to-end release-times and deadlines. This paper describes algorithms to schedule a class of systems where all the tasks execute on different processors in turn in the same order. This end-to-end scheduling problem is known as the flow-shop problem. We present two cases where the problem is tractable and evaluate a heuristic for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…CaDAnCE does not affect the QoS behavior of operational strings. When components are promoted from a lower-criticality operational string to a higher-criticality one, component criticality is also increased to match the criticality of the higher-criticality string, which is essential to avoid criticality inversion at deployment-time [6]. Since CaDAnCE promotes components only at deployment time, it does not change the actual real-time QoS configurations (such as thread priorities, component placement and collocation) used later during runtime, i.e., CaDAnCE does not affect the QoS behavior of operational strings.…”
Section: Characteristics Of Cadancementioning
confidence: 99%
“…CaDAnCE does not affect the QoS behavior of operational strings. When components are promoted from a lower-criticality operational string to a higher-criticality one, component criticality is also increased to match the criticality of the higher-criticality string, which is essential to avoid criticality inversion at deployment-time [6]. Since CaDAnCE promotes components only at deployment time, it does not change the actual real-time QoS configurations (such as thread priorities, component placement and collocation) used later during runtime, i.e., CaDAnCE does not affect the QoS behavior of operational strings.…”
Section: Characteristics Of Cadancementioning
confidence: 99%
“…A number of methods for modeling the real-time behavior of dataflow applications have been developed for multiprocessor and distributed systems [4,12,15,23]. Typically, such applications are modeled as directed acyclic graphs (DAGs), with nodes denoting tasks and edges denoting producer/consumer relationships.…”
Section: Introductionmentioning
confidence: 99%
“…(8) follows directly from the delay property of maximum rate function [1]. Using (8), subsequent servers can be analyzed. Once all the delays at individual servers are obtained, we can substitute (7) into (1) to compute the delay for connection j.…”
Section: Server Analysismentioning
confidence: 99%
“…The generic solution for guaranteeing endto-end delay bounds in distributed systems consists of connection-oriented communications with some form of admission control and traffic regulation (typically based on packet scheduling at the network interface) [7][8][9][10][11][12][13][14]18]. Supplementary research in protocols for guaranteed services on networks is reported in [15][16][17].…”
Section: Introductionmentioning
confidence: 99%